Relationship Between Semantic and Aesthetic Dimensions of Contemporary Iraqi Painting and Modernity Arts: Relación entre las dimensiones semántica y estética de la pintura iraquí contemporánea y las artes de la modernidad - HUSSEIN, Hamid; HAMZAH, Talib; MUBARAK, Ali (Utopía y Praxis Latinoamericana, 2021)
ABSTRACT The modern European artists tackle the emergent perceptual realization that is reflected in art through realistic forms to complete the inherent cognitive energies; imagination and intuition. The inner worlds find what produces a comprehensive overall vision that is capable of creating its penetrating cognitive world to the hidden feeling. The present study consists of the methodological framework which includes the problem of whether contemporary Iraqi painting includes modern connotations of intellectual and aesthetic descriptions of modern European schools or not, the significance, the objectives, the limits, the theoretical framework, results, and recommendations. RESUMEN Los artistas europeos modernos abordan la realización perceptiva emergente que se refleja en el arte a través de formas realistas para completar las energías cognitivas inherentes; imaginación e intuición. Los mundos internos encuentran lo que produce una visión global integral que es capaz de crear su mundo cognitivo penetrante al sentimiento oculto. El presente estudio consiste en el marco metodológico que incluye el problema de si la pintura iraquí contemporánea incluye connotaciones modernas de descripciones intelectuales y estéticas de las escuelas europeas modernas o no, el significado, los objetivos, los límites, el marco teórico, los resultados y las recomendaciones.